An analytical surface potential modeling of fully-depleted symmetrical double-gate (DG) strained-Si MOSFETs including the effect of interface charges - Sarangi S.; Santra A.; Bhushan S.; Gopi K.S.; Dubey S.; Tiwari P.K. (My University, 2025)
A two-dimensional (2D) surface potential model for a fully-depleted symmetrical double-gate strained- Si MOSFET damaged with oxide interface charges is being proposed. The damage due to the hot carrier effect, is a common phenomenon in short-channel devices. The parabolic potential approximation is utilized to solve 2D Poisson's equation in the channel region. The developed surface potential model incorporates the effect of both positive as well as negative interface charges. The effects of interface charge density, extent of the damaged region and the strain variations in the channel region on the surface potential have been studied comprehensively. The model results are in reasonable agreement with simulation results of ATLAS™, a numerical simulator by Silvaco Inc. © 2013 IEEE.